IMPLEMENTASI KEBIJAKAN STANDARISASI SARANA DAN PRASARANA KERJA DI LINGKUNGAN PEMERINTAH DAERAH KABUPATEN BANDUNG (Studi Tentang Kendaraan Dinas Operasional ): Array - Enung Khusufmawati; Heru Nurasa; Mohammad Benny Alexandri (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
Implementation of the Policy on Standardization of work facilities and infrastructure regarding the use of KDO in the Bandung Regency Government, there are many problems so that the BPK finds the distribution of vehicles compared to the number of employees who are entitled to use these vehicles. The purpose of this study is to analyze how the implementation of the policy of standardization of work facilities and infrastructure in Bandung Regency (study on the use of KDO). The method in this study uses a qualitative research method with a descriptive research design and tends to use an inductive approach to analysis. Where the author tries to find an understanding of an object by using the existing theory will be developed with the data collected. The model from Grindle is considered relevant to be used as a research theory with two important variables that can affect the implementation process, namely the content of the policy and the implementation environment in relation to the desired degree of change. understanding of the implementors, coupled with the administration of KDO so far that has not been maximized, despite all these efforts to resolve the KDO problem, the character factor of the leader involved in implementing this policy is still considered to be less firm so that it seems that there has been omission in KDO administration so far, thus giving rise to the existence of form of non-compliance from the implementers.